1977
DOI: 10.1080/03015521.1977.10425959
|View full text |Cite
|
Sign up to set email alerts
|

Use of insecticides during autumn to control soldier fly larvae and increase pasture production

Abstract: A range of insecticides, their formulations, rates of application, and method of distribution were tested. Carbofuran and isophenphos proved most effective, but control was poor (46-66% mortality in autumn trials). There was no difference between seed treatment and granular formulations although spraying high rates (6.0 kg a.i.z'ha) on to existing pasture proved effective. Results indicate that during winter-spring pasture production was related to larval population and that a population reduction of 1000 larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The pattern 'Of infestation in New Zealand has been one of slow spread and increase to hi'gh population levels (Pottinger 1973, Wilcocks 1974a), but recently widespread P'OPulation decl·ines have ,been evident (Robertson & Bl'ank 1981). Pasture damage is caused at larval densities exceeding 200{}-3000 per m' (Wilcocks 1974b, Dixon 1977.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern 'Of infestation in New Zealand has been one of slow spread and increase to hi'gh population levels (Pottinger 1973, Wilcocks 1974a), but recently widespread P'OPulation decl·ines have ,been evident (Robertson & Bl'ank 1981). Pasture damage is caused at larval densities exceeding 200{}-3000 per m' (Wilcocks 1974b, Dixon 1977.…”
Section: Introductionmentioning
confidence: 99%
“…Under the moderate grazing treatments which did not coincide with the peak flights, the seasonal mean densities ranged from 900 to 4800 larvae per square metre. The higher levels were within the range at which pasture losses can become measurable (Dixon 1977). The estimated mean densities of the moderately grazed plots outside peak flights at each period were used to calculate the results presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…pastures in the northern North Island. It is extremely difficult to control the insect with insecticides (Robertson 1979) and control by intensive cultivation (Wilcocks & Hewitt 1971) or minimal or no cultivation with drilled seed and insecticide (Dixon 1977) are costly procedures to apply (Davison et al 1979). Kain & Burton (1975) suggested that control of soldier fly was possible by defoliation during the flight periods (late spring and autumn) and mowing at these times resulted in a reduction (75-83%) in the numbers of new (small) larvae establishing in the short compared with the rank pasture.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are many reports of establishment failures attributed to pests and improved seedling establishment from insecticide, molluscicide and nematicide use when direct drilling pastures. Dixon & Davison (1975), Rowe & MacKay (1975), Dixon (1977) and Davison et al (1979) establish that larvae oflnopus rubriceps Macquart (Diptera: Stratiomyzidae) move onto rows of seedlings and concluded that this movement enhances the effectiveness of insecticides placed with the seed. The use of herbicide to remove existing plant cover before drilling resulted in improved larval control as the insects were forced to feed on the toxic seedlings.…”
Section: Introductionmentioning
confidence: 99%